Indeks Sanitasi dan Faktor-Faktor Penentunya Pada Area Urban Poverty Kota Bandung(Studi Kasus: Kecamatan Bandung Wetan, Kota Bandung) - Jasmine Raissa Rachmadina; Mindriany Syafila; Dyah Wulandari Putri (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Universal access to water, sanitation and hygiene (WASH) is a basic human right that reflects well-being. However, disparities in access to WASH persist in Indonesia, influenced by economic factors, education and sanitation behaviours. In urban areas, urban poverty exacerbates the gap in access to WASH, with the urban poor vulnerable to inadequate sanitation due to economic and knowledge constraints. In Kecamatan Bandung Wetan, which is located in the middle of Bandung city, this condition is still found, where low-income groups are vulnerable to the fulfilment of proper sanitation. The sanitation index is a tool to evaluate the sanitation system in a community. The sanitation index was analysed using exploratory factor analysis. The variables that make up the index are based on the 5 pillars of Community-Led Total Sanitation (CLTS). The results of the analysis show that the sanitation index in Kecamatan Bandung Wetan is built by the factors of clean water use, household welfare, low prevalence of environmental diseases, faecal user interface, and final disposal of household waste, with the highest sanitation index value found in Kelurahan Citarum.